Future Development of Indonesian Education: A Review of the Urgency of Reconstructing Instruction Designs for Islamic Religious Education - Muji Agus Sofiyandi; Moh. Nurhakim; Khozin Khozin (Universitas Muhammadiyah Enrekang, 2024)
This study discusses the urgency of reconstructing Islamic religious education in Indonesia. It constitutes a meticulous literature review. Despite its literature review nature, the research is grounded in a clearly formulated problem statement, ensuring that the gathered scholarly literature is highly relevant to the research objectives. What is the urgency of reconstructing the design of Islamic religious education learning to shape the future of education in Indonesia? All data was obtained through online searches using Google Scholar, ensuring the accuracy and credibility of the sources. The applied analysis is content analysis. This study demonstrates that the urgency of reconstructing the design of Islamic Religious Education learning in shaping the future of education in Indonesia can be thematically mapped as follows: 1) Rapid Technological Growth and Globalisation; 2) Dynamics of Social and Cultural Changes; 3) Capturing Students' Interest and Involvement; 4) Enhancement of Religious Conceptual Understanding; 5) Development of Character and Morality; 6) Preparation for Future Challenges; 7) Inclusive Learning and Tolerance. This study contributes to strengthening the significant rationale for the necessity of reconstructing the design of Islamic religious education.